Structural Behavior of a Fixed-End Arched Cellular Steel Beam without Lateral Support - Qiujun Ning; Jiawei Lu; Shaojuan Li; Xiaosong Lu (Buildings, 2024)
The arched cellular beam has the advantages of both the solid-web arch and the straight beam with web opening, and has become increasingly admired by architects in recent years. In this paper, four arched cellular beam specimens are designed using an orthogonal test method (OTM) with a three-factor and two-level approach. Firstly, the static loading test is carried out to analyze the mechanical response of the arched cellular beam under concentrated load. Then, a numerical analysis based on ABAQUS finite element (FE) software is carried out. The results show that the simulation results agree well with the test results, which indicates the accuracy of the simulation analysis method. Finally, the buckling load of the arched cellular beam under three different loads is calculated using the variable parameter FE analysis. Combined with the range analysis in the OTM, the influence of the target factor on the buckling load of the arched cellular beam is determined. The results show that the order of the factors affecting the out-of-plane elastic buckling is rise–span ratio > web height–thickness ratio > diameter–depth ratio.